Ash Cenosphere from Solid Fuels Combustion. Part 2: Significant Role of Ash Cenosphere Fragmentation in Ash and Particulate Matter Formation - Li, Yi; Gao, Xiangpeng; Wu, Hongwei (American Chemical Society, 2013)
A set of experiments was carried out to combust pulverized pyrite particles (38-45 µm) at 600 °C in a drop-tube furnace system. Ash and particulate matter (PM) samples were collected using a cyclone followed by a Dekati low-pressure impactor (DLPI) at various residence times (0.4, 0.7, 0.9, and 1.1 s) to investigate the fragmentation behavior of ash cenospheres and their roles in ash evolution and PM formation. At a residence time of 0.4 s, the production of ash cenospheres is limited. As the residence time increases, the formation of ash cenospheres increases substantially. Ash cenosphere fragments of various sizes also increase significantly, clearly indicating the enhanced fragmentation of ash cenospheres at a longer residence time (e.g., 1.1 s). Such ash cenosphere fragmentation also results in a substantial increase in the yield of PM with an aerodynamic diameter less than 10 µm (PM10). The results in this study provide direct experimental evidence as the first time in the field to demonstrate the significant role of ash cenosphere fragmentation in ash and PM10 formation.